Cytophaga hutchinsonii SprA and SprT Are Essential Components of the Type IX Secretion System Required for Ca2+ Acquisition, Cellulose Degradation, and Cell Motility - Gao, Lijuan; Tan, Yahong; Zhang, Weican; Qi, Qingsheng; Lu, Xuemei (Frontiers in Microbiology, 2021)
The type IX secretion system (T9SS) is a novel protein secretion system, which is found in and confined to the phylum Bacteroidetes. T9SS is involved in the secretion of virulence factors, cell surface adhesins, and complex biopolymer degrading enzymes to the cell surface or extracellular medium. Cytophaga hutchinsonii is a widely distributed bacterium, which is able to efficiently digest cellulose and rapidly glide along the solid surfaces. C. hutchinsonii has a full set of orthologs of T9SS components. However, the functions of most homologous proteins have not been verified. In C. hutchinsonii, CHU_0029 and CHU_2709 are similar in sequence to Flavobacterium johnsoniae T9SS components SprA and SprT, respectively. In this study, the single deletion mutants of chu_0029 (sprA) and chu_2709 (sprT) were obtained using a complex medium with the addition of Ca2+ and Mg2+. Single deletion of sprA or sprT resulted in defects in cellulose utilization and gliding motility. Moreover, the ΔsprA and ΔsprT mutants showed growth defects in Ca2+ - and Mg2+ - deficient media. The results of ICP-MS test showed that both the whole cell and intracellular concentrations of Ca2+ were dramatically reduced in the ΔsprA and ΔsprT mutants, indicating that SprA and SprT are both important for the assimilation of trace amount of Ca2+. While the assimilation of Mg2+ was not obviously influenced in the ΔsprA and ΔsprT mutants. Through proteomics analysis of the cell surface proteins of the wild type and mutants, we found that the ΔsprA and ΔsprT mutants were defective in secretion of the majority of T9SS substrates. Together, these results indicate that SprA and SprT are both essential components of C. hutchinsonii T9SS, which is required for protein secretion, Ca2+ acquisition, cellulose degradation, and gliding motility in C. hutchinsonii. Our study shed more light on the functions of SprA and SprT in T9SS, and further proved the link between the T9SS and Ca2+ uptake system.